The Journal of Pediatric and Neonatal Individualized Medicine (JPNIM) was awarded a “Journal of high cultural value” prize by the Italian Ministry of Culture: the reasons of success - Fanos, Vassilios (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2024)
Dear Readers, I would like to share with you the news that, in November 2023, the Journal of Pediatric and Neonatal Individualized Medicine (JPNIM) was awarded a “Journal of high cultural value” prize by the Italian Ministry of Culture, through the General Directorate for Libraries and Copyright (with the decree D.D.G. n. 812, 16/11/2023). This is a great achievement as, in the biological-medical field, only a total of 3 journals were awarded by this decree. This Editorial shows information about JPNIM, JPNIM Open Access policy, JPNIM Editorial Board, JPNIM indexing and archiving, the fact that JPNIM is the official journal of many Societies, JPNIM publication, JPNIM website views and JPNIM metrics.